2022
DOI: 10.1021/acs.langmuir.2c01021
|View full text |Cite
|
Sign up to set email alerts
|

Formation of n-Hexane-in-DMF Nonaqueous Pickering Emulsions: ABC Triblock Worms versus AB Diblock Worms

Abstract: Nonaqueous Pickering emulsions exhibit promising applications in many industrial areas but have been relatively less studied in the past. In this study, n-hexane-in-DMF nonaqueous Pickering emulsions stabilized by core cross-linked copolymer worms with mixed shells are demonstrated for the first time. Core cross-linked copolymer worms with mixed shells were prepared by seeded reversible addition–fragmentation chain transfer (RAFT) quasi-solution polymerization. Specifically, polystyrene-poly­(4-vinylpyridine) … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4

Citation Types

0
4
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 7 publications
(4 citation statements)
references
References 65 publications
0
4
0
Order By: Relevance
“…It is expected that seeded PISA can overcome the limitations of traditional PISA and expand new horizons toward PISA. [67,[71][72][73][74][75][76][77][78][79][80][81] Briefly, two steps are involved in a typical seeded PISA that include the preparation of seeds via PISA and the subsequent chain extension under heterogeneous polymerization conditions, generating triblock or multiblock copolymer nanoparticles with unique morphologies and surface properties. In addition, seeded PISA also enables the control over the size of polymer particles.…”
Section: Introductionmentioning
confidence: 99%
“…It is expected that seeded PISA can overcome the limitations of traditional PISA and expand new horizons toward PISA. [67,[71][72][73][74][75][76][77][78][79][80][81] Briefly, two steps are involved in a typical seeded PISA that include the preparation of seeds via PISA and the subsequent chain extension under heterogeneous polymerization conditions, generating triblock or multiblock copolymer nanoparticles with unique morphologies and surface properties. In addition, seeded PISA also enables the control over the size of polymer particles.…”
Section: Introductionmentioning
confidence: 99%
“…7 cores and polystyrene/poly(lauryl methacrylate) mixed shells, which could stabilize n-hexane-in-dimethylformamide Pickering emulsions. 8 In addition to the particle size, the geometry shape of solid particles plays vital roles in regulating the packing density, orientation at the interfaces, and stability of the emulsion droplets. Compared with the spheric counterpart, the stabilizing effect of nonspherical solid particles (e.g., flake and ellipsoid) is related with the different steric effect and capillary forces on the oil/water interface.…”
Section: ■ Introductionmentioning
confidence: 99%
“…Different solid particles, such as latex particles, inorganic nanoparticles, and clay particles have been used to stabilize the interface of emulsions with a variety of functionalities . Sun et al prepared polymer worms containing cross-linked poly­(4-vinylpyridine) cores and polystyrene/poly­(lauryl methacrylate) mixed shells, which could stabilize n -hexane-in-dimethylformamide Pickering emulsions . In addition to the particle size, the geometry shape of solid particles plays vital roles in regulating the packing density, orientation at the interfaces, and stability of the emulsion droplets.…”
Section: Introductionmentioning
confidence: 99%
“…Recently, several research groups have reported MSPN stabilized Pickering emulsions. [40][41][42][43] Studies revealed that MSPNs exhibited excellent emulsifying performances owing to adaptive wettability at liquid-liquid interfaces. Adaptive wettability benefited from the different affinities of shells to different phases.…”
Section: Introductionmentioning
confidence: 99%